Responsibility Sharing between Adolescents with Type 1 Diabetes and Their Caregivers: Importance of Adolescent Perceptions on Diabetes Management and Control - Vesco, Anthony T. (Oxford University Press, 2010)
Objective To analyze associations between factor scores for caregiver responsibility for direct and indirect diabetes management tasks with glycemic control and blood glucose monitoring (BGM) frequency. Methods Two hundred and sixty one adolescents with type 1 diabetes and their caregivers completed the Diabetes Family Responsibility Questionnaire (DFRQ). Data on diabetes management (e.g., BGM frequency) and glycemic control (e.g., A1c values) were obtained. Results Confirmatory factor analysis of the DFRQ revealed two factors—direct and indirect management tasks. Multivariate analyses demonstrated that adolescent perception of greater responsibility sharing with caregivers on direct management tasks was significantly associated with higher BGM frequency. Conclusions Adolescents who perceive greater caregiver responsibility, particularly around direct management tasks, engage in better diabetes management. Implications of these findings include designing interventions that encourage and sustain caregiver responsibility through adolescence and make explicit the contribution of caregivers.